Analysis of the tactical performance factors in elite beach volleyball - Ferrer, D. M.; Aranda, C. E.; Gutierrez, L. M. C.; Antonio, J.; Turpin, P.; Gomis, M. J. G. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: To analyze the tactical performance factors of counterattack in the elite senior category of beach volleyball. Methods: Data were obtained from the recording of 34 matches played from 28 July to 6 August 2017 in the city of Vienna. The observed variables were related to the counterattack in elite players of beach volleyball. The free software used to register the variables was LongoMatch (v.1.3). Subsequently, the data were processed with the SPSS statistical package (V.22). Results: There are significant differences in the attacks of the blocker between points 15-21 of the set and in the effectiveness of the defenders and blockers depending on whether they play the ball in the natural side or not. Moreover, defenders present differences in the type of attack (hard or feint) depending on the time of the set. Conclusions: Learning about the dynamics of the tactical aspects of the counterattack in beach volleyball is necessary to understand the development of the competition.